The Bacteriophage EF-P29 Efficiently Protects against Lethal Vancomycin-Resistant Enterococcus faecalis and Alleviates Gut Microbiota Imbalance in a Murine Bacteremia Model - Cheng, Mengjun; Liang, Jiaming; Zhang, Yufeng; Hu, Liyuan; Gong, Pengjuan; Cai, Ruopeng; Zhang, Lei; Zhang, Hao; Ge, Jinli; Ji, Yalu; Guo, Zhimin; Feng, Xin; et al. (Frontiers in Microbiology, 2017)
Enterococcus faecalis is becoming an increasingly important opportunistic pathogen worldwide, especially because it can cause life-threatening nosocomial infections. Treating E. faecalis infections has become increasingly difficult because of the prevalence of multidrug-resistant E. faecalis strains. Because bacteriophages show specificity for their bacterial hosts, there has been a growth in interest in using phage therapies to combat the rising incidence of multidrug-resistant bacterial infections. In this study, we isolated a new lytic phage, EF-P29, which showed high efficiency and a broad host range against E. faecalis strains, including vancomycin-resistant strains. The EF-P29 genome contains 58,984 bp (39.97% G+C), including 101 open reading frames, and lacks known putative virulence factors, integration-related proteins or antibiotic resistance determinants. In murine experiments, the administration of a single intraperitoneal injection of EF-P29 (4×105 PFU) at 1 h after challenge was sufficient to protect all mice against bacteremia caused by infection with a vancomycin-resistant E. faecalis strain (2×109 CFU/mouse). E. faecalis colony counts were more quickly eliminated in the blood of EF-P29-protected mice than in unprotected mice. We also found that exogenous E. faecalis challenge resulted in enrichment of members of the genus Enterococcus (family Enterococcaceae) in the guts of the mice, suggesting that it can enter the gut and colonize there. The phage EF-P29 reduced the number of colonies of genus Enterococcus and alleviated the gut microbiota imbalance that was caused by E. faecalis challenge. These data indicate that the phage EF-P29 shows great potential as a therapeutic treatment for systemic VREF infection. Thus, phage therapies that are aimed at treating opportunistic pathogens are also feasible. The dose of phage should be controlled and used at the appropriate level to avoid causing imbalance in the gut microbiota.